The Acoustic Field Distribution Inside the Ultrasonic Ring Array - STASZEWSKI, Wiktor; GUDRA, Tadeusz; OPIELINSKI, Krzysztof J. (Archives of Acoustics, 2018)
This paper presents and analyses the results of a simulation of the acoustic field distribution in sectors of a 1024-element ring array, intended for the diagnosis of female breast tissue with the use of ultrasonic tomography. The array was tested for the possibility to equip an ultrasonic tomograph with an additional modality - conventional ultrasonic imaging with the use of individual fragments (sections) of the ring array. To determine the acoustic field for sectors of the ring array with a varying number of activated ultrasonic transducers, a combined sum of all acoustic fields created by each elementary transducer was calculated. By the use of MATLAB software, a unique algorithm was developed, for a numerical determination of the distribution of pressure of an ultrasonic wave on any surface or area of the medium generated by the concave curvilinear structure of rectangular ultrasound transducers with a geometric focus of the beam. The analysis of the obtained results of the acoustic field distribution inside the ultrasonic ring array used in tomography allows to conclude that the optimal number of transducers in a sector enabling to obtain ultrasound images using linear echographic scanning is 32 ≤ $n$ ≤ 128, taking into account that due to an increased temporal resolution of ultrasonic imaging, this number should be as low as possible.